Critical success factors in early secondary education : an analysis of variables within the school environment which influence the development and progress of students entering the first year of their secondary education - Wilson, David (Trinity College (Dublin, Ireland). School of Education, 2006)
The primary purpose of this piece of research was to identify data trends which influenced the experience of students from their entry into year one of secondary school to the completion of their Junior Certificate exams at the end of year three. The focus of attention was a theory that factors within the school environment influenced students and that, as a result, their individual performances were dependent to some degree on a wide range of variables. If it were possible to identify these variables, the results could be used to advise and assist parents, teachers, students or indeed a number of educational stakeholders. The school chosen for the purposes of the study was an all boys independent school, located in south Dublin. The annual intake of year one students was just under 100 and each year group were looked after by a ‘Year Head’. These year heads provided much of the daily information relating to behaviour, attendance and punctuality and also acted as a reference point for weekly briefings regarding the progress of the group. Class teachers, form teachers and extra-curricular staff also provided information which was added to the continuous stream of formal input and which was valuable in terms of providing a complete account of each student’s experiences.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin